День Соборності України: історико-політологічні дискусії (до 100-річчя Соборності України (22.01.1919 – 22.01.2019). Вип. 6 - Хмельницький інститут ПрАТ «ВНЗ «МАУП» (My University, 2019)
У збірнику наукових праць вміщено статті, виголошені на засіданні Всеукраїнської науково-практичної конференції «День Соборності України: історико-політологічні дискусії» (до 100-річчя Української революції 1917–1921 рр.). Авторами статей розкрито такі питання: історія української державності; Українська Центральна Рада та Директорія в документах; українська національно-демократична революція 1917–1921 рр.: перебіг і причини поразки; День Соборності України: початки ідеї соборності; передумови возз’єднання українських земель; Акт возз’єднання українських земель: політологічний аналіз; День Соборності України: історія та сучасність. The collection of scientific works contains articles presented at the meeting of the All-Ukrainian Scientific and Practical Conference “Day of Unity of Ukraine: Historical and Political Discussions” (to the 100th anniversary of the Ukrainian Revolution of 1917–1921). The authors of the articles addressed the following issues: history of Ukrainian statehood; Ukrainian Central Rada and Directory in documents; Ukrainian National Democratic Revolution of 1917–1921: course and causes of defeat; Day of Unity of Ukraine: the beginnings of the idea of ​​unity; prerequisites for the reunification of Ukrainian lands; Act of Reunification of Ukrainian lands: political scientific analysis; Day of Unity of Ukraine: history and present.